Planning health promotion programs an intervention mapping approach - Bartholomew Eldredge, L. Kay; Parcel, S. Guy; Kok, Gerjo; Gottlieb, Nell H. (Jossey-Bass, 2011)
This thoroughly revised and updated third edition of Planning Health Promotion Programs provides a powerful, practical resource for the planning and development of health education and health promotion programs.